2022
DOI: 10.1182/blood.2021012788
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cholesterol homeostasis in hematopoietic malignancies

Abstract: Cholesterol is a vital lipid for cellular functions. It is necessary for membrane biogenesis, cell proliferation and differentiation. In addition to maintaining cell integrity and permeability, increasing evidence indicates a strict link between cholesterol homeostasis, inflammation and haematological tumors. This makes cholesterol homeostasis an optimal therapeutic target for hematopoietic malignancies. Manipulating cholesterol homeostasis either interfering with its synthesis or activating the reverse choles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 103 publications
0
20
0
Order By: Relevance
“…In this study, we expanded the notion of co‐existing functional subsets of Mo within TME of DLBCL, revealing striking association of the LXRα transcript (encoded by NR1H3 gene) expression with the M1 phenotype of Mo with putative anti‐tumor effect. Accumulating data highlighted the relevance of LXRs in anti‐cancer immune surveillance and described mechanisms of LXR axis activity in diverse immune cytotypes 32,33 . Particularly, the function of LXRα remains controversial as it can regulate a broad range of activities in specific subsets of accessory cells, such as Mo, in the context of various human cancers 34 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we expanded the notion of co‐existing functional subsets of Mo within TME of DLBCL, revealing striking association of the LXRα transcript (encoded by NR1H3 gene) expression with the M1 phenotype of Mo with putative anti‐tumor effect. Accumulating data highlighted the relevance of LXRs in anti‐cancer immune surveillance and described mechanisms of LXR axis activity in diverse immune cytotypes 32,33 . Particularly, the function of LXRα remains controversial as it can regulate a broad range of activities in specific subsets of accessory cells, such as Mo, in the context of various human cancers 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Pathway enrichment analysis with these 235 genes determined IL-2/ STAT5 signaling pathway was the most highly enriched. In addition, it was reported that other enriched pathways including mechanistic target of rapamycin complex 1 (mTORC1) signaling pathway, androgen response, cholesterol homeostasis, estrogen response, and interferon gamma response were related to AML (44)(45)(46)(47)(48). Prognostic models based on these gene pathways might be alternative candidates for predicting prognosis of AML patients.…”
Section: Discussionmentioning
confidence: 99%
“…In conditions of high cholesterol levels, INSIG, SCAP and SREBP2 form a stable trimolecular complex in the ER, thereby blocking the export and activation of SREBP2 and finally blocking the de novo cholesterol synthetic route. Moreover, excess oxysterols or desmosterol bind and activate the LXR/RXR heterodimer, which in turn activates specific LXR target genes, such as ATP-binding cassette transporters A1 and G1 (ABCA1 and ASCG1), allowing excess cholesterol to be transported to the liver and excreted as bile acids ( Figure 1 ) ( 78 ).…”
Section: Cholesterol Metabolism In Hematological Malignanciesmentioning
confidence: 99%